Prospective associations of appetitive traits at 3 and 12 months of age with body mass index and weight gain in the first 2 years of life. Issue 1 (December 2015) - Quah, Phaik; Chan, Yiong; Aris, Izzuddin; Pang, Wei; Toh, Jia; Tint, Mya; Broekman, Birit; Saw, Seang; Kwek, Kenneth; Godfrey, Keith; Gluckman, Peter; Chong, Yap; et al.
Abstract Background Appetitive traits in childhood such as food responsiveness and enjoyment of food have been associated with body mass index (BMI) in later childhood. However, data on appetitive traits during infancy in relation to BMI in later childhood are sparse. We aimed to relate appetitive traits in infancy to subsequent BMI and weight gain up to 24 months of age. Methods Data of 210 infants from the Singapore GUSTO mother-offspring cohort was obtained. The Baby Eating Behavior Questionnaire (BEBQ) and the Child Eating Behavior Questionnaire (CEBQ) were administered to mothers when their offspring were aged 3 and 12 months respectively. Height and weight of offspring were measured at ages 3, 6, 9, 12, 15, 18 and 24 months. The association of appetitive traits with both BMI z-score and weight gain were evaluated using multivariate linear regression. Results Food responsiveness at 3 months was associated with higher BMI from 6 months up to 15 months of age (p < 0.01) and with greater weight gain between 3 and 6 months of age (p = 0.012). Slowness in eating and satiety responsiveness at 3 months was significantly associated with lower BMI at 6 months (p < 0.01) and with less weight gain between 3 to 6 months of age (p = 0.034). None of the appetitive traits at 12 months were significantly associated with BMI or weight gain over any time period. Conclusion Early assessment of appetitive traits at 3 months of age but not at 12 months of age was associated with BMI and weight gain over the first two years of life. Trial registration Clinical Trials identifierNCT01174875